Desenvolvimento de simulador de ocultações estelares: aplicação ao caso do possível planeta 9 - Ferrante, Wellington Gomes (2024)
Trans-Neptunian objects are bodies in the Solar System that have semi-major orbital axis greather than that of Neptune. The study of these bodies can provide information about the origin and evolution of the Solar System. For example, a significant concentration in the orbital properties of some of these objects, among the most distant known, was noted. This can be explained by the existence of a large body, called Planet 9, which is still unknown. Brown e Batygin (2021) determined, through numerical simulations, possible orbits for the planet. Searches and analyzes of observational data have been carried out in an attempt to detect it, but none have been successful to date. Assuming that Planet 9 is discovered in the near future, it will become important to determine its physical characteristics, to better understand its origin and its influence on TNOs. Stellar occultation is an observational technique that has been used to determine characteristics of distant objects in the Solar System, such as TNOs. It allows you to determine the size and shape with great precision, in addition to checking the presence of satellites, rings or atmosphere around the occulting object. This work presents the development of a stellar occultation simulator, which generates realistic occultation light curves, considering the physical parameters of the involved objects, as well as the instruments and atmospheric conditions and associated noises. Such simulations were analyzed with SORA (GOMES-JúNIOR et al., 2022), a Python library for reducing and analyzing stellar occultations, which allowed us to verify the influence of the main variables involved in the construction of occultation light curves by the planet. The results of simulations of stellar occultations by the possible Planet 9 are presented, for which the physical and orbital properties proposed in the literature were used.